2023
DOI: 10.3390/jcm12175453
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Associated Factors of Sedentary Behavior by Diabetes Mellitus Status: A Nationwide Cross-Sectional Study

Dong Kee Jang,
Hyung Seok Nam,
Mina Park
et al.

Abstract: This study aimed to identify the lifestyle and comorbidity factors associated with sedentary behavior by diabetes mellitus (DM) status. A total of 17,832 participants aged ≥50 years from the Korea National Health and Nutrition Examination Survey were included. Factors associated with long sedentary time (LST, ≥420 min/day) in individuals with and without DM (non-DM) were assessed. Among individuals with DM, LST was independently associated with excessive alcohol drinking (OR, 1.34; 95% CI, 1.02–1.74) and cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…This finding may be justified by the social uncertainty and instability that cohabiting individuals may experience. Although a certain study indicated that the association between diabetes mellitus and occupational activity was inconsistent (30), participants in the present study without occupational activity were associated with type 2 diabetes mellitus. This result, which implies a low socioeconomic status attributable to unfavourable lifestyle factors (obesity), is consistent with previous studies which found that people from high-income countries with low incomes were more likely to have type 2 diabetes (31).…”
Section: Discussioncontrasting
confidence: 72%
“…This finding may be justified by the social uncertainty and instability that cohabiting individuals may experience. Although a certain study indicated that the association between diabetes mellitus and occupational activity was inconsistent (30), participants in the present study without occupational activity were associated with type 2 diabetes mellitus. This result, which implies a low socioeconomic status attributable to unfavourable lifestyle factors (obesity), is consistent with previous studies which found that people from high-income countries with low incomes were more likely to have type 2 diabetes (31).…”
Section: Discussioncontrasting
confidence: 72%
“…On the other hand, in older adults, the sedentary behavior facilitates body weight gain, harms the function of the cardiovascular system, impairs the immune system responses, and increases the risk of suffering psychological and mental disorders (e.g., depression, psychological stress, and anxiety) and low resilience (14)(15)(16). Likewise, authors have previously identified that the sedentary behavior is a strong independent risk factor to suffer cardiovascular diseases in older adults with diabetes (17). The previous information emphasizes the need to practice physical activity in healthy and commorbidiy older adults, this kind of intervention was widely recommended throughout social distancing (9, 18-23), the recommendations included practice aerobic exercise (e.g., walking) complemented by balance and strength exercises (21,23).…”
Section: Introductionmentioning
confidence: 99%